2011
DOI: 10.1055/s-0031-1295650
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Related Infection and Pathogens of Umbilical Venous Catheterization in a Neonatal Intensive Care Unit in China

Abstract: We studied the incidence of umbilical venous catheterization (UVC)-related infection and pathogens in a neonatal intensive care unit (NICU) in China. Patients were grouped into <2000-g UVC or <2000-g non-UVC groups or ≥2001-g UVC or ≥2001-g non-UVC groups. Blood culture and umbilical root skin swab culture were taken following UVC insertion and extraction. UVCs were removed after 7 days and cultures of UVC tips were performed then. A total of 516 patients were enrolled. The incidence of UVC-related septicemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…(11) Another study from China in 2012 yielded a rate of 13.6 per 1,000 umbilical catheter days. (12) The Canadian Neonatal Network UVC-associated CABSI rate seemed to have stayed stable at around 7.8-8.2 per 1,000 catheter days in another review published in 2015, (9) as part of a comparison with the peripherally inserted central catheter (PICC) line.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(11) Another study from China in 2012 yielded a rate of 13.6 per 1,000 umbilical catheter days. (12) The Canadian Neonatal Network UVC-associated CABSI rate seemed to have stayed stable at around 7.8-8.2 per 1,000 catheter days in another review published in 2015, (9) as part of a comparison with the peripherally inserted central catheter (PICC) line.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective cohort study that evaluated the outcome of introducing a standardised PICC and care bundle showed that infants with UVC lasting over seven days had a greater risk of central line-associated bloodstream infection (odds ratio 5.48) than those with UVC lasting seven days or less. (19) However, a recent Cochrane review by Gordon et al (3) that investigated early planned removal of UVCs within two weeks to prevent infection included only one studythat by O'Hara et al (12)(13)(14) CI 0.01-7.94). More infants in the early planned removal group than in the expectant management group required percutaneous insertion of a central catheter (or PICC).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that a very low birth weight and a longer duration of antibiotic therapy were risk factors for umbilical arterial catheter-related sepsis [ 32 ]. A study from China showed that the incidence of umbilical venous catherization related septicemia was at 9.5% [ 33 ]. The most common organisms associated with umbilical catheterization related septicemia in our study were Staphylococcus aureus and coagulase-negative Staphylococcus, which is similar to what was reported by previous studies [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As outbreak of severe sepsis is one of the most compelling challenges in SCNs of different regions, standardised neonatal ward management to prevent nosocomial infections is now mandatory and becoming a routine measure which requires well-controlled sterilisation facilities, hand hygiene, isolation space, restricted use of antibiotics, among other things, implemented as part of the hospital quality assurance. Umbilical vascular-accessed and peripheral-inserted central catheterisation are being more and more used for VLBW infants with restricted length of indwelling to prevent nosocomial infection in SCNs 34. Other pathogen-related infections are also encountered in daily service, ranging from hepatitis B virus35 and HIV, to mycoplasma, chlamydia and syphillis 36.…”
Section: Neonatal Infection and Sepsismentioning
confidence: 99%